CONTRIBUTING WITH DESIGN OF EXPERIMENT THEORY TO QUALITY - Hornikova, Adriana; Bas, Goekcen; Sagbas, Binnur; Durakbasa, Numan M. (TECHNICAL UNIV CLUJ-NAPOCA, 2011)
The Design of Experiment theory can contribute to quality and quality improvement within the six sigma strategy approach, here we used the DMAIC approach. Paper utilizes the wide spread out six sigma strategy to quality/business quality to analyse the implementation possibilities of theory of design of experiment. The theory contributes nearly in each of the five steps of six sigma strategy (define, measure, analyse, improve, control) with different designs and purpose of application. Our paper further points out and discusses the possibilities of implementing the theory of design of experiment through various statistical methods that are implemented in different steps of six sigma strategy. The second part of this contribution gives brief introduction to designs with different aims and their application, like screening for influential effects, seeking a functional, prediction etc. Useful is also the utilization of statistical software with the capability of design of experiment and evaluation. Authors have chosen the modular system SAS JMP (R) for design of experiment and presented it to the reader (SAS stands for Statistical Analysis Software).
Keywords: Design of experiment; statistical analysis; six sigma; TQM; Business & Economics